Comparison of asprosin immunoreactivity in endometrial hyperplasia and grade-1 endometrial adenocarcinoma: A retrospective case-control study - Senocak, Ahmet; Yavuzkir, Seyda; Atilgan, Remzi; Yurt, Nurdan; Balta, Hilal; Kuloglu, Tuncay; Cim, Bunyamin (Galenos Publ House, 2025)
Objective: It has been demonstrated that asprosin, a glucogenic adipokine released by white adipose tissue, contributes to the pathophysiology of cancer and disorders associated with it. The aim of this study was to compare the immunoreactivity of asprosin in grade I endometrial adenocarcinoma and in endometrial hyperplasia (EH) with and without atypia. Materials and Methods: A total of 80 cases previously diagnosed with grade 1 endometrial adenocarcinoma and EH with and without atypia, and for which paraffin blocks were obtained, were included in the study. The resulting paraffin blocks were sectioned again and immunostained for asprosin. A total of 80 cases were divided into 4 groups according to their histopathological diagnoses. Group (G) 1 (n=20): proliferative endometrium, G2 (n=20): EH without atypia, G3 (n=20): EH with atypia, G4 (n=20): Grade 1 endometrial adenocarcinoma. Endometrial samples from 80 patients were sectioned, and asprosin immunoreactivity was evaluated by immunohistochemical staining under a light microscope. Results: In comparison to the proliferative endometrium group, the grade I endometrial adenocarcinoma group had considerably increased asprosin immunoreactivity. However, between the proliferative endometrium group and the groups with endometrial hyperplasia, without atypia, and endometrial hyperplasia, with atypia, there was no significant difference in asprosin immunoreactivity. Conclusion: While asprosin immunoreactivity scores are higher in grade I endometrial adenocarcinomas, they are similar to those of the proliferative endometrium in cases of EH with and without atypia, suggesting that energy metabolism contributes to the development of cancer arising from endometrial hyperplasia. Asprosin immunoreactivity can be studied as a marker to predict the progression of EH to cancer.
Endometriyal hiperplazi ve grade-1 endometriyal adenokarsinomdaki asprosin immünoreaktivitesinin karşılaştırılması: Retrospektif bir olgu-kontrol çalışması
Keywords: Immunohistochemistry; asprosin; endometrial hypeplasia; endometrial cancer